Nurses’ Spirituality Improves Caring Behavior - Abu Bakar; Nursalam Nursalam; Merryana Adriani; Kusnanto Kusnanto; Siti Nur Qomariah; Laily Hidayati; Ika Nur Pratiwi; Lailatun Ni'mah (International Journal of Evaluation and Research in Education (IJERE), 2017)
Caring was the behavior provide assistance holistically to individuals. In fact, nurses Caring behaviors made only modest, yet an art in nursing care which should always be a nurse. The good personality and spiritual be one of the factors that affect the formation of nurses Caring behaviors. Spiritual was the passion or impulse that comes out from within themselves to do the noble. The research objective was explained a spiritual relationship nurses with nurses caring behaviors. The research design was used cross sectional. The population in this researchs were associate nurses in the ward. A sample were taken of 88 nurses with consecutive sampling technique. Data collection was done at the General Hospital of Haji Surabaya, Al Irsyad General Hospital Surabaya and Muhammadiyah Gresik Hospital. Data collection was used questionnaire, with multivariate data analysis Structural Equation Modeling- Partial Least Square (PLS-SEM). The results showed no significant relationship between demographic with spiritual nurses. Demographic indicators for the hypothesis test was psychological, length of work, education, and wards. Demographics nurses with nurse caring no significant relationship. Spiritual nurses significant relationship with the caring nurses at 7.061. These results indicated that modeling should be done was draw line from the spiritual to the caring nurses and the others deleted. The conclusion of the research was the spiritual nurses significant relationship with the nurses caring behaviors. Suggestions have to do is always give spiritual training to nurses as one of supporting the implementation of nursing care.